Navigating Legal Challenges: Implementing Nullity Verdict in Indonesia - Senja Pramudia (Pancasila and Law Review, 2023)
Zero verdict is a criminal sentence imposed on a person who has received a maximum sentence but must be retried due to certain cases so that the criminal sentence given is zero or the maximum limit. Nil verdicts are still rarely known by the Indonesian people. The question in the community is why judges do not add punishment to criminal offenders who have been proven legally guilty of committing a criminal offense, in essence. Nil verdict is explicitly contained in the concept of concursus realis based on Article 67 of the Criminal Code that imposing the death penalty in such a way does not receive additional punishment if other criminal offenses are found at any time. The research method used is normative juridical, conducted by studying, viewing, and examining legal regulations such as the Criminal Code and Circular Letter Number 1 of 2022 concerning the Enforcement of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2022. The results showed that a nil verdict is very appropriate to be applied to defendants whose verdicts are sentenced to death, such as the cases of Muhammad Natsir and Heru Hidayat, so if there are other cases, they must be sentenced to Nil. This makes the Defendant previously sentenced to imprisonment for 20 years, not increase to life. Another problem is the lack of inter-court administration integration, resulting in overlapping criminal sanctions and exceeding 20 years. The absorption principle in concursus realis is sharpened. It is necessary to review the level between legally binding crimes and crimes that have just been revealed based on higher criminal threats so that the application of zero verdicts achieves the principles of legal certainty, Justice, and practicality. In this research, the author focuses on developing knowledge about zero verdicts that ordinary people can understand.